The Relationship between Aging Anxiety and Attitudes towards the Elderly among Health Care Providers in Mazandaran Province in 2018 - Tayebeh Abdollahi; Nasibeh Zanjari; Yadollah Abolfathi Momtaz; Ahmad Delbari (Golestan University of Medical Sciences, 2021)
Background: According to the World Health Organization, aging anxiety decrease life expectancy and causes disease in old age. Negative attitude towards the older adults is a major factor associated with aging anxiety. Therefore, the present study aimed to determine the relationship between attitudes towards the older adults and fear of aging in the health care providers of Social Security Organization's hospitals in Mazandaran province in 2018. Methods: We conducted the present cross-sectional study on 232 health care providers of hospitals of Social Security Organization in Mazandaran province in 2018, selected them by stratified random sampling according to the job categories, and included them in the study. We utilized the Anxiety about Aging Scale (AAS) by Lasher and Faulkender and Koganchr('39')s Attitude toward Old People Scale (KAOPS) to collect data. We analyzed the data in SPSS16 using Pearson correlation, independent t-test, and one-way analysis of variance. Results: The participantschr('39') mean age was 37.85±6.40 years and the mean of aging anxiety was 67.90±10.60. Among the four subscales of aging anxiety, the highest fear was related to "fear of loss" (23.7±4.5) and then "fear of physical appearance" (21.25±4.65), and the lowest was related to "fear of the  older people " (10.12± 3.25). Despite the slightly higher mean aging anxiety among nursing and midwifery staff than medical staff, it was not statistically significant. Findings indicated that aging anxiety had a negative and significant relationship with attitudes towards the older adults in health care providers (r=0.35, P=0.001). Conclusion: Given the high aging anxiety in health care providers and its importance in providing services for the older adults as well as the quality of their old age, we suggest promoting the health care providers' positive attitudes towards the older adults through in-service training courses.